Anemia, Hyperglycemia, and Reduced Left Ventricular Ejection Fraction Improve the GRACE Score’s Predictability for In-hospital Mortality in Acute Coronary Syndrome; Single-Centre Cross-Sectional Study - Turu' Allo IJ; Pramudyo M; Akbar MR (Open Access Emergency Medicine)
Iswandy Janetputra Turu’ Allo,1,2 Miftah Pramudyo,1 Mohammad Rizki Akbar1 1Department of Cardiology and Vascular Medicine, Faculty of Medicine Universitas Padjadjaran/Dr. Hasan Sadikin General Hospital, Bandung, Indonesia; 2Faculty of Medicine Universitas Pendidikan Indonesia, Bandung, IndonesiaCorrespondence: Iswandy Janetputra Turu’ Allo, Email iswandy21001@mail.unpad.ac.id; iswandy.t.a@gmail.comPurpose: This study investigates the predictive value of incorporating anemia, hyperglycemia, and left ventricular ejection fraction (LVEF) into the Global Registry of Acute Coronary Events (GRACE) score for in-hospital mortality in Acute Coronary Syndrome (ACS).Patients and Methods: We conducted a single-center, cross-sectional study involving 634 ACS patients admitted to Dr. Hasan Sadikin General Hospital between 2021 and 2023. Anemia was defined as hemoglobin < 13 g/dL in men and < 12 g/dL in women, while hyperglycemia was indicated with random blood glucose (RBG) ≥ 200 mg/dL at admission. Patients with LVEF < 50% were classified as having reduced LVEF. The primary outcome was in-hospital mortality. Model goodness-of-fit was assessed using R2 and the Hosmer-Lemeshow’s test. The predictive accuracy of the GRACE score alone and combined with these parameters were evaluated through receiver operating characteristic curve analysis, an area under the curve (AUC), and concordance (C)-statistics. Reclassification improvement was quantified using continuous net reclassification improvement (cNRI) and integrated discrimination improvement (IDI).Results: Among 634 patients (mean age 58.10± 11.08 years old; 80.3% male), anemia, hyperglycemia, and reduced LVEF were observed in 197 (31.1%), 123 (19.4%), and 364 (57.4%) patients, respectively. The in-hospital mortality rate was 6.6%. Regression analysis identified nine predictors of mortality, with anemia, hyperglycemia, and reduced LVEF confirmed as independent predictors. The GRACE score showed an AUC of 0.839 (95% confidence interval/CI 0.77– 0.0.90). Incorporating anemia, hyperglycemia, and reduced LVEF increased the AUC to 0.862 (95% CI 0.81– 0.91), enhancing predictive accuracy (p = 0.590). Combining these variables yielded an NRI of 0.075 (p = 0.070) and an IDI of 0.035 (p = 0.029).Conclusion: Incorporating anemia, hyperglycemia, and reduced LVEF into the GRACE score improves its predictive capacity for in-hospital mortality in ACS patients. The modified GRACE score offers a more robust risk stratification tool for clinical practice and decision-making.Plain Language Summary: Predicting in-hospital mortality risk in acute coronary syndrome (ACS) is crucial for clinical decision-making and patient outcomes. We investigated whether incorporating anemia, hyperglycemia and reduced left ventricular ejection fraction (LVEF) into the existing Global Registry of Acute Coronary Events (GRACE) score improves its ability to predict in-hospital mortality. Based on 634 ACS patients, the study suggests that including these clinical parameters improved the GRACE score’s predictive ability for in-hospital mortality. The modified version demonstrated better risk stratification, thus allowing the identification of high-risk patients more effectively. We highlight the potential of integrating these variables into the GRACE score; however, further research is necessary to validate the modified score across populations.Keywords: acute coronary syndrome, anemia, GRACE risk score, hyperglycemia, in-hospital mortality, left ventricular ejection fraction